PENILE PARAFFINOMA RECONSTRUCTION WITH SCROTAL FLAP AND SURGICAL OUTCOME: A CASE REPORT - Putra, Ida Bagus Oka Widya; Wahyudi, Irfan; Rodjani, Arry (Indonesian Journal of Urology, 2019)
Objective: To present a case of penile paraffinoma reconstructed with scrotal flap. Case presentation: We report a case of 33-year-old male patient with penile paraffinoma. The patient had a history of injecting liquid paraffin into his penis two times – at 6 months and 2 months prior to his admission to the hospital. His IIEF-5 was 10 (moderate erectile dysfunction). The penile shaft was circumferentially enlarged. There was ulceration on the ventral aspect with signs of inflammation on the surrounding skin. Discussion: We perform a complete excision of paraffinoma. The raw surface was repaired with a one-stage scrotal flap. At six-month follow up, the wound was good, and the patient was able to micturate normally. He was able to achieve painless erection, and IIEF-5 score was improved. Conclusion: A one-stage scrotal flap may offer a good choice in defect closure in penile paraffinoma reconstruction.